Educational Inclusion: biopolitical approach related to the bicentennial - Juan Carlos Echeverri-Alvarez (Universidade Federal do Rio Grande do Sul, 2021)
This paper studies the historical relationship between education and society based on a problematic element - inclusion. The commemoration of independence in American countries is addressed to show that different forms of educational inclusion seen today must be analyzed from the perspective of the form of power that made them possible and necessary for the last two hundred years, that is, the liberal power. The concepts of biopolitics and governance are used theoretically and methodologically. It is showed that educational inclusion is not an altruistic contingency of power but a condition of possibility of its constant validity. Additionally, its inherent obligation to impose exclusion and promote inclusion is part of the current logic according to which ruling also entails letting others live and facilitating death for them.